2016
DOI: 10.1177/00333549161310s113
|View full text |Cite
|
Sign up to set email alerts
|

Expanded HIV Testing and Linkage to Care: Conventional vs. Point-of-Care Testing and Assignment of Patient Notification and Linkage to Care to an HIV Care Program

Abstract: Lead organizations such as UCM were able to assist and oversee HIV screening and linkage to care for HIV patients diagnosed at community sites. HIV screening and linkage to care can be accomplished by incorporating standard testing for HIV into routine medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
0
21
0
2
Order By: Relevance
“…Participants' suggestions to disconnect testing from clinical settings and limit interactions with health care providers (i.e., testing kiosks, HIVST kits, community testing) may assist with reducing negative perceptions about HIV testing experiences. While non-clinical testing may help reduce stigma, it is also important to identify ways to improve linkage to care for people tested in community settings [26,27]. Faith-based and community-based leaders could not only help change norms about HIV as a taboo topic, but also serve as an ongoing local voice for testing promotion and awareness, filling in the gaps between larger public events like health fairs that promote HIV testing.…”
Section: Discussionmentioning
confidence: 99%
“…Participants' suggestions to disconnect testing from clinical settings and limit interactions with health care providers (i.e., testing kiosks, HIVST kits, community testing) may assist with reducing negative perceptions about HIV testing experiences. While non-clinical testing may help reduce stigma, it is also important to identify ways to improve linkage to care for people tested in community settings [26,27]. Faith-based and community-based leaders could not only help change norms about HIV as a taboo topic, but also serve as an ongoing local voice for testing promotion and awareness, filling in the gaps between larger public events like health fairs that promote HIV testing.…”
Section: Discussionmentioning
confidence: 99%
“…Providers’ concern for follow up on abnormal tests further inhibits the willingness to offer screening, particularly in settings such as the emergency department (ED) where they are more likely to encounter patients who do not otherwise access the healthcare system [39, 4446]. Establishing institutional policies that support providers in these areas have been successful in overcoming these barriers, including personnel trained in notification and linkage procedures [4750].…”
Section: Care Continuum Entry Interventionsmentioning
confidence: 99%
“…PLWH who are aware of their HIV infection but not retained in care are now understood to contribute to a significant number of new transmission events, and efforts for re-engagement can begin with the testing event [57]. Universal screening programs implemented in places such as the ED have found that up to 50% of positive HIV tests occur in those already aware of their diagnosis, many of whom are out of care [47]. This group has been difficult to link back to care and novel strategies are being identified to address this problem such as the CDC’s Data to Care program funded through local health departments, as well as using surveillance data to identify and reach these individuals [5860].…”
Section: Care Continuum Entry Interventionsmentioning
confidence: 99%
“…Indeed, EDs have become an important setting for routine HIV testing because ED patients are often disproportionately affected by HIV and may have limited access to primary care. [4][5][6][7] With routine opt-out HIV testing, EDs have uncovered thousands of new HIV diagnoses and have engaged patients at each stage of the HIV care continuum. [8][9][10][11][12][13] EDs, however, often offer little in regards to HIV prevention services for those who test negative for HIV.…”
Section: Introductionmentioning
confidence: 99%